Efeito do ultra-som terap??utico pulsado na prolifera????o e atividade gelatinol??tica de c??lulas musculares. - Ribeiro, Rafael (2009)
Ultrasound has been one of the most widely and frequently used electro-therapeutic modalities for over 60 years. However, its effectiveness in treating pain, musculoskeletal disorders and soft tissue lesions remains questionable and its therapeutic potential is not fully established. In order to contribute to knowledge in this field, the objectives of the present study were to carry out a systematic review on this subject and perform an in vitro study for the assessment of the effect of therapeutic pulsed ultrasound on the proliferation and gelatinolytic activity of skeletal muscle cells (C2C12). Ultrasound was tested at frequencies of 1 and 3 MHz, powers of 0.2 and 0.5 W/cm2 and pulsed mode at 20% with application periods of 2 and 5 min. Cell proliferation was measured indirectly 72 hours after irradiation by assessing mitochondrial activity using the MTT method. Gelatinolytic activity in the supernatant of the cell cultures was assessed by zymography, complimented with densitometry analysis of bands that furnished gelatin hydrolysis. The control group was made up of cell cultures not submitted to ultrasound. The data were treated statistically with a significance level of 0.5% (p ??? 0.05 - ANOVA-Dunnet). The systematic review revealed considerable controversy among the results and parameters employed, which renders definitive conclusions regarding the potential of ultrasound on muscle tissue impossible. The experiments revealed no significant differences in cell proliferation between ultrasound-treated myoblasts and control cultures after 72 hours of incubation. The same was true in the densitometry analysis of the gels. Thus, there is a need for further investigations in order to gain a better understanding of the biochemical, cellular and organic reactions triggered by ultrasound as well as for the establishment standards of frequency, intensity, exposure time and application mode of this therapeutic resource.